Lithobius (Monotarsobius) franciscorum sp. nov., a new lithobiid species from the Altai, with a key to the Central Asian species of the subgenus (Chilopoda: Lithobiomorpha) - Dányi, László; Tuf, Ivan H. (Zootaxa, 2012)
Lithobius franciscorum sp. nov. is described and illustrated based on specimens from the Kazakh part of the Altai Moun-tains. The new species is characterized principally by the group of club-like setae situated on the males’ last femora, afeature unique in the whole genus. According to this character, the species appears to be closely related to the group ofspecies with similar setae on the males’ last tibiae, while the female of the new species resembles Lithobius nordenskioldiiStuxberg, 1876, with which it is compared. Keys to the Central Asian Monotarsobius Verhoeff, 1905 species’ males andfemales are presented as well. Three nomina nova are introduced, Lithobius farzalievae nom. nov. for Lithobius minimusFarzalieva, 2006, Lithobius dobrorukai nom. nov. for Lithobius mongolicus Dobroruka, 1960 and Lithobius insolens nom. nov. for Lithobius insolitus Farzalieva, 2006.